1993
DOI: 10.1172/jci116657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amino acids on substrate selection, anaplerosis, and left ventricular function in the ischemic reperfused rat heart.

Abstract: The effect of aspartate and glutamate on myocardial function during reperfusion is controversial. A beneficial effect has been attributed to altered delivery of carbon into the citric acid cycle via substrate oxidation or by stimulation of anaplerosis, but these hypotheses have not been directly tested. "C isotopomer analysis is well suited to the study of myocardial metabolism, particularly where isotopic and metabolic steady state cannot be established. This technique was used to evaluate the effects of aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…It has been speculated that anaplerotic flux may serve as a biosensor between the cytoplasm and the mitochondria (11,36,39,43,48). Furthermore, evidence suggests a role for anaplerosis in the regulation of contractile function in the heart (15,23,30,42,49). Recent studies have also shown that flux through pyruvate carboxylase regulates amino acid synthesis (33,34) and may be important in controlling cell growth (34,43).…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that anaplerotic flux may serve as a biosensor between the cytoplasm and the mitochondria (11,36,39,43,48). Furthermore, evidence suggests a role for anaplerosis in the regulation of contractile function in the heart (15,23,30,42,49). Recent studies have also shown that flux through pyruvate carboxylase regulates amino acid synthesis (33,34) and may be important in controlling cell growth (34,43).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of net anaplerosis from glutamine/glutamate would require the demonstration of simultaneous cataplerosis evidenced by (i) stimulation of gluconeogenesis in liver and kidney, or (ii) release of CAC intermediates and aspartate from non-gluconeogenic tissues. The effect of anaplerosis from glutamine/glutamate on cardiac function has been controversial, with positive and negative reports of improvement of cardiac function in animal models (Jessen et al 1993;Khogali et al 1998).…”
Section: Glutamine/glutamatementioning
confidence: 99%
“…4). While the crucial role of anaplerosis for hepatic gluconeogenesis is self-evident, investigations in the heart suggested that stimulating anaplerosis from exogenous substrates could become part of the treatment of myocardial reperfusion injury and other cardiomyopathies (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%